IN VITRO ANTIMICROBIAL STUDIES OF TRYCHYSPERMUM AMMI - SAVITA AGGARWAL; SANJAY GOYAL (International Journal of Pharma and Bio Sciences, 2012)
The antimicrobial activity of essential oil and different solvent extract of seed of Trachyspermum ammi were assayed in vitro by agar disc diffusion against bacterial species. Hydrodistillation of seeds of Trachyspermum ammi using clevenger apparatus was carried out. Extraction of seeds of Trachyspermum ammi with different solvents (Petroleum ether, Benzene, chloroform & Methanol), were also carried out in order of their increasing polarity. Antimicrobial activity of essential oil and solvent extracts of Trachyspermum ammi were done using Salmonella typhi, Escherichia coli, Lactobacillus & Bacillus lichenifomis. The results showed that the essential oil showed better antimicrobial activity in comparison to extracts. Among the different solvent extracts, chloroform extract showed more antimicrobial activity in comparison to the other extract. Methanol extract did not show any antimicrobial activity.